A Framework for Inclusion and Diversity in Environmental Citizen ScienceReview of: Citizen Science: Public Participation in Environmental Research; Janis L. Dickinson and Rick Bonney; (2015). Comstock Publishing Associates, Ithaca, NY. 304 pages. - Jillian Mochnick (American Society for Microbiology, 2016)
Review of: Citizen Science: Public Participation in Environmental Research; Janis L. Dickinson and Rick Bonney; (2015). Comstock Publishing Associates, Ithaca, NY. 304 pages. A review of the new book "Citizen Scienece: Public Participation in Environmental Research" by Janis L. Dickinson, Professor of Natural Resources at Cornell University and Arthur A. Allen Director of Citizen Science at the Cornell Lab of Ornithology, and Rick Bonney, Director of Program Development and Evaluation at the Cornell Lab of Ornithology. These authors amongst many contributors provide the theory, framework, and practice to citizen science projects. This text provides resources to disseminate projects with diverse goals to engage the general public in the scientific process and to study the natural world.